Business Development of Small & Medium Sized Companies in Sustainable Buildings - PARDALIS, GEORGIOS (My University, 2017)
This thesis proposes a business canvas that is based on findings from six small and mediumsized craftsmen companies in the Swedish construction industry and the examination of example cases of similar sized companies from other countries. That proposed business canvas could be followed by other companies of similar size in the Swedish construction industry, in order them to enter the market of sustainable buildings and achieve an increase in competence, resources and size. The increasing awareness regarding climate change and energy use, especially when we talk about buildings, and the development of the legal framework in building constructions, leave space for the development of innovative ideas that could improve the energy performance of the existing building stock. Energy renovations are a promising market for companies of small and medium size. There are a variety of barriers though that those companies are required to overcome in order to enter successfully this market. Barriers related to steering mechanisms, financing of such projects, cooperation and networking with other companies, competence development in the concepts of energy efficiency, client understanding and client approach need to be addressed and solutions are required to be found. Through the examination of a project oriented towards energy efficiency that have been performed in Belgium, and with the use of examples cases of small and medium sized companies that have tried to enter the market of energy renovations, a better knowledge regarding the problems of this market and the steps that a company is required to make to enter it, is acquired. Additionally, with the use of results from interviews with small and medium sized craftsmen companies that operate in Sweden an understanding on how those companies work until know, what kind of customer relationships and business network they develop and how they think of their future in the level of the local markets related to sustainable building is gained. The results show that companies first and foremost need to build competence and trust to themselves that they can lead and coordinate projects related to the energy efficiency of buildings. The most important barriers that companies need to overcome are building relationships of trust with their potential customers, find ways to communicate better and to broader audience concepts related to energy efficiency, expand their existing networks and include in them experts from different areas related to their work. All these will allow them to grow in size and capital. In order to achieve that, concepts like value proposition, customer segment, key activities, key partners, key resources, customer relationship, channels of communication, distribution and sales, cost structure, and revenue stream, are explained and analysed so them to be placed on a business canvas that companies could follow.
Keywords: Samhällsbyggnadsteknik; Civil Engineering